A Patient with Acute Cervical Cord Injury and COVID-19: A First Case Report - Pattanakuhar, Sintip (Am J Phys Med Rehabil, 2020)
During the pandemic of Coronavirus disease 2019 (COVID-19), it is possible for rehabilitation physicians and personnel to take care of patients with concurrent spinal cord injury (SCI) and COVID-19. Here, we describe a case of acute cervical SCI resulting in complete tetraplegia C5 American Spinal Injury Association (ASIA) Impairment Scale (AIS) A with unrecognized, acute respiratory syndrome coronavirus 2 (SAR-CoV-2) infection. This resulted in large-scale quarantines of related surgical and rehabilitation staff, and the unexpected death of the patient despite receiving the treatments according to the standard guideline. Rehabilitation personnel who take care of acute SCI patients with COVID-19 should consider the effect of SCI on the course of COVID-19, the effect of COVID-19 and its treatments on the course of SCI, and risks of SAR-CoV2 transmission between patients and rehabilitation staff, to continue providing safe and effective rehabilitation programs.